Some remarks about series - Janaszak, Tadeusz (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2016)
This paper presents a proof of the classical theorem of the theory of series. This proof would be used in lectures on the series theory.
Didactics of Mathematics, 2016, No. 13(17), s. 17-24
Keywords: series; convergent; divergent series; harmonic series